A Proprioceptive Ability Factor Underlying All Proprioception Tests? Response to Tremblay (2013). Issue 1 (August 2014) - Han, Jia; Waddington, Gordon; Adams, Roger; Anson, Judith
There may be a higher-order processing system (or general proprioceptive ability) which receives inputs from various proprioceptive sources across different body areas. In general, Tremblay's (2013) criticisms are overly based on peripheral proprioceptors, and do not represent alternative interpretations or the data generated by studies evaluating those interpretations.